European Union Charter of Fundamental Rights; European Convention on Human Rights - Comparative Analysis of Interpretation and Application by the European Court of Justice and the European Court of Human Rights - Ryabova, Victoria O. (Moscow journal of international law, 2014)
The negotiators, representatives of the Council of Europe member states and of the European Union, ﬁ nalised the draft accession agreement of the European Union to the European Convention on Human Rights in spring, 2013. Due to the fact that the possibility of the accession is now not conﬁ ned to the provisions of Protocol 14 to the European Convention on Human Rights and article 6 of the Treaty on European Union, the questions of cooperation between the ECJ and the ECtHR and interpretation and application of the main European acts on human rights - the European Union Charter of Fundamental Rights and the European Convention on Human Rights - are becoming more and more important.